2017
DOI: 10.1038/nmeth.4408
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory stimuli differentiate adapting circuit topologies

Abstract: Adapting pathways consist of negative feedback loops (NFLs) or incoherent feedforward loops (IFFLs), which we show can be differentiated using oscillatory stimulation: NFLs but not IFFLs generically show ‘refractory period stabilization’ or ‘period skipping’. Using these signatures and genetic rewiring we identified the circuit dominating cell cycle timing in yeast. In C. elegans AWA neurons we uncovered a Ca2+-NFL, diffcult to find by other means, especially in wild-type, intact animals. (70 words)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 42 publications
1
72
0
Order By: Relevance
“…Our first example, motivated by the paper [14], where similar models appear, is a negative feedback system which consists of two species X and Y such that X enhances the production of Y and Y inhibits the production of X. The concentrations of X and Y at time t are denoted respectively by x = x(t) and y = y(t).…”
Section: The Two Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our first example, motivated by the paper [14], where similar models appear, is a negative feedback system which consists of two species X and Y such that X enhances the production of Y and Y inhibits the production of X. The concentrations of X and Y at time t are denoted respectively by x = x(t) and y = y(t).…”
Section: The Two Modelsmentioning
confidence: 99%
“…"dynamic phenotypes") can provide further insight into the structure of biological systems. Recent examples include scale invariance or "fold-change detection" [10,11,12], non-monotonic behavior under monotonic inputs [13], refractory period stabilization [14], and non-entrained solutions or "period skipping" when stimulii are periodic [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, life evolved to thrive in the presence of gradual changes (Harvey and Smith, 2009;Sorre et al, 2014), and recent studies have demonstrated that many cells respond differently to inputs of equal magnitudes based upon specific variations in input kinetics, such as different temporal frequencies (Albeck et al, 2013;Ashall et al, 2009;Cai et al, 2008;Hao and O'Shea, 2012;Hersen et al, 2008;Mettetal et al, 2008;Wang et al, 2012) or different spatial gradients (Harvey and Smith, 2009). A few pioneering studies have even demonstrated that different kinetic stimulations can dramatically affect intracellular signaling dynamics to create distinct cell phenotypes (Averbukh et al, 2018;Cai et al, 2004;Heltberg et al, 2019;Mettetal et al, 2008;Mitchell et al, 2015;Rahi et al, 2017;Shimizu et al, 2010;Sorre et al, 2014;Thiemicke et al, 2019;Zhang et al, 2019) (Figure 1A). The fact that different kinetics of the same environmental inputs create such different responses offer a new opportunity to generate a wider and richer range of signaling pathway dynamics, while using current experimental assays that measure only a small number of signaling proteins.…”
Section: Introductionmentioning
confidence: 99%